Silicon Leaf Fertilization Promotes Biofortification and Increases Dry Matter, Ascorbate Content, and Decreases Post-Harvest Leaf Water Loss of Chard and Kale - De Souza, José Zenóbio [UNESP]; De Mello Prado, Renato [UNESP]; Silva, Sylvia Letícia de Oliveira; Farias, Thiago Palhares; Neto, Júlio Garcia [UNESP]; Souza Junior, Jonas Pereira de [UNESP] (Taylor & Francis, 2019)
This study aimed to evaluate the effects of silicon (Si) leaf fertilization in different concentrations and sources on the production and quality of chard and kale. We carried out two experiments with chard and kale under a completely randomized design with four replicates in a 2 × 4 factorial scheme and two sources of silicon: potassium silicate and stabilized sodium potassium silicate with four concentrations of Si: 0.00; 0.84; 1.68 and 2.52 g L −1 . We performed three leaf sprays every 10 days. The chard and kale were harvested at 48 and 54 days after transplanting the seedlings, respectively. Silicon leaf fertilization is important for leafy vegetables like chard and kale because it increases the content and the accumulation of Si and the growth and production of the vegetables. It also improved growth, productivity, and quality. The Silicon leaf fertilization of 2.52 g L −1 in the form of potassium silicate was the most notable.
Keywords: abiotic stress; beneficial element; Beta vulgaris var cicla; Brassica oleracea var acephala; potassium silicate